L4-L5-S1 human dermatomes: a clinical, electromyographical, imaging and surgical findings Dermátomos humanos L4, L5 e S1: achados clínicos, eletromiográficos, de imagem e cirúrgicos - Antonio Tadeu de Souza Faleiros; Luiz Antonio de Lima Resende; Marco Antonio Zanini; Heloisa Amélia de Lima Castro; Roberto Colichio Gabarra (Arquivos de Neuro-Psiquiatria)
There is substantial controversy in literature about human dermatomes. We studied L4, L5, and S1 inferior limb dermatomes by comparing clinical signs and symptoms with conduction studies, electromyographical data, neurosurgical findings, and imaging data from computerized tomography (CT) or magnetic resonance imaging (MRI). After analyzing 60 patients, we concluded that L4 is probably located in the medial aspect of the leg, L5 in the lateral aspect of the leg and foot dorsus, and S1 in the posterior aspect of the backside, tight, leg and plantar foot skin. This is the first time that these human dermatomes have been evaluated by combined analysis of clinical, electromyographical, neurosurgical, and imaging data. Há controvérsia na literatura sobre os dermátomos humanos. Estudamos dermátomos do membro inferior comparando sinais e sintomas com estudos eletromiográficos, de imagem e achados cirúrgicos. Analisando 60 pacientes, concluímos que o dermátomo L4 provavelmente está localizado na região medial da perna, o dermátomo L5 na região lateral da perna e dorso do pé, e o dermátomo S1 na nádega, região posterior da coxa e da perna e na região plantar. Este é o primeiro estudo que os dermátomos do membro inferior foram analisados através de dados clínicos, eletromiográficos, imagem e achados cirúrgicos.